Proposed Cellular Function of the Human FAM111B Protein and Dysregulation in Fibrosis and Cancer - Arowolo, Afolake; Malebana, Moses; Sunda, Falone; Rhoda, Cenza (Frontiers in Oncology, 2022)
FAM111B gene mutations are associated with a Hereditary Fibrosing Poikiloderma known to cause Poikiloderma, Tendon Contracture, Myopathy and Pulmonary Fibrosis (POIKTMP). In addition, the overexpression of FAM111B has been associated with cancer progression and poor prognosis. This review inferred the molecular function of this gene's protein product and mutational dysfunction in fibrosis and cancer based on recent findings from studies on this gene. In conclusion, FAM111B represents an uncharacterised protease involved in DNA repair, cell cycle regulation, and apoptosis. Also, the dysregulation of this protein ultimately leads to fibrotic diseases like POIKTMP and cancers via the disruption of these cellular processes by the mutation of the FAM111B gene. Hence should be studied in the context of these diseases as a possible therapeutic target.